Ibn Hajar Al-Asqalani’s Perspective on Gharar in Economic Transactions - Tio Arithama Rohman; Siti Nurhasanah Munawaroh (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
Transactions in Islamic economics must uphold justice, transparency, and the avoidance of uncertainty (gharar). A key challenge is managing uncertainty in high-risk transactions that may cause unjust profit, lack of clarity, and disputes. Ibn Hajar Al-Asqalani, a renowned scholar in fiqh and hadith, provides valuable insights on gharar that remain relevant to contemporary economic practices. This study aims to explore his perspective on gharar in economic transactions. Gharar, prohibited in Qur’an Surah An-Nisa verse 29 and Hadith Muslim no. 1513, is rejected unanimously by classical Islamic schools. Al-Ghazali emphasized honesty and transparency to avoid gharar, while fiqh al-mu‘amalah outlines essential pillars and conditions to regulate transactions. This research employs literature study using Ibn Hajar’s works and related scholarly contributions. Ibn Hajar defines gharar as ambiguity regarding the object or contract before execution. He prohibits excessive (fahish) gharar but tolerates minor (yasir) gharar if it does not harm either party, often resolved through the option of khiyar. He highlights that gharar arises when the essential pillars and conditions of sale are not met, thus stressing justice and realism in contracts. Imam Malik, by contrast, permits customary practice (urf) as long as it aligns with justice and avoids harm. In modern practice, maqasid al-shari’ah serves to secure public benefit (maṣlaḥah) and prevent harm (mafsadah). Economic actors are encouraged to uphold these principles, especially in online and derivative transactions. The findings suggest that Ibn Hajar’s framework provides a foundation for analyzing high-risk contracts in Islamic economics